Tracing the Emergence of the Italian Verb volerci. - Russi, Cinzia (Quaderni d'italianistica, 2009)
The present article has two major objectives. First, it reveals the results of an original empirical analysis of Old Italian (OI) material (twenty texts from the thirteenth and fourteenth centuries), which I carried out in order to trace the emergence and reconstruct the early distributional pattern of the Italian verb volerci 'be necessary, be required, need', and also 'take', as in 'it takes time', 'it takes patience', etc. The second goal of the study is to put forward a tentative proposal about the type of construction from which volerci originated. The OI texts examined are listed in Table 1 below. I start with providing a basic description of the structural properties and the semantic domain of volerci (§ 2; a more detailed discussion is found in Russi "On Italian volerci"). Next, I introduce, comment on, and discuss the attestations of volerci found in the OI corpus I analyzed (§ 3). I then sketch my account of the development of volerci from volere (§ 4). I conclude summarizing the main points and drawing attention to some issues that call for further investigation (§ 5).